COVID-19 infection control practices in designated quarantine hotels in Hong Kong SAR (China), 2020–2022: key elements in preparing for the next pandemic - Ma, Edmond Siu-keung; Chen, Hong; Chuang, Shuk Kwan (Western Pacific Surveillance and Response, 2025)
Problem: Despite the widespread use of designated quarantine hotels to minimize the transmission of COVID-19 from imported cases, there is scant literature on the infrastructure and operational requirements of such facilities.Context: Travellers to Hong Kong Special Administrative Region (SAR) (China) were required to undergo quarantine in designated hotels for up to 21 days. Prior to operation, all these hotels were modified and hotel staff received structured training in infection control practices.Action: We conducted retrospective reviews of the procedures and operational protocols that were followed to convert and manage commercial hotels as quarantine hotels during the early part of the pandemic. We also reviewed the training provided and compliance monitoring. Finally, we reviewed intra-hotel outbreak investigations that were conducted between April 2021 and June 2022.Outcome: Designated quarantine hotels received 842 510 quarantined travellers from December 2020 to October 2022. Ten outbreaks were reported, affecting 28 guests (0.003%) and two staff. Prompt epidemiological investigation and action stopped further transmission.Discussion: In Hong Kong SAR (China), designated quarantine hotels successfully minimized COVID-19 transmission from imported cases to the community and should be considered as part of integrated response plans for future pandemics. Based on our COVID-19 pandemic experience, we recommend specifying requirements for quarantine centres and hotels to ensure adequate ventilation inside guest rooms and corridors, functioning drainage systems and the adoption of stringent infection control practices. We also recommend the installation of closed-circuit television cameras in all common areas to support compliance monitoring and outbreak investigation.
Keywords: COVID-19; quarantine; infection transmission; infection control; pandemics; Hong Kong